The Gold Bag - Wells, Carolyn, 1862-1942 (Salt Lake City, UT : Project Gutenberg, 2001)
(3z(BThe Gold Bag(3y (Bby Carolyn Wells is a detective novel written during the early 20th century. The story revolves around the investigation of the mysterious murder of a wealthy man, Joseph Crawford, in his home. The narrative unfolds through the perspective of Herbert Burroughs, a young detective who aspires to emulate the renowned detective Fleming Stone, who possesses an extraordinary talent for deduction. At the start of the novel, we are introduced to Burroughs just as he receives the urgent call to investigate the crime scene in West Sedgwick. Upon arriving, he learns about Crawford's final hours and discovers a gold-mesh bag in the office that could hold vital clues. The opening portion sets the stage for an intricate web of relationships, with significant characters such as the enigmatic Florence Lloyd, Crawford's niece, whose engagement to Gregory Hall complicates matters further. As Burroughs navigates through suspicious testimonies and the initial evidence, the foundation is laid for a classic whodunit where each character's motives will need to be scrutinized, and the quest for truth will deepen. (This is an automatically generated summary.)s
Release date is 2001-10-01
Produced by An Anonymous Project Gutenberg Volunteer, and David Widger
Keywords: Detective and mystery stories; Stone, Fleming (Fictitious character) -- Fiction